Composición florística de las lomas de Queneto: Un área con potencial para la conservación en la región La Libertad, Perú - Cuba-Melly, Norton (2025)
This study addresses the vascular flora composition of the Queneto lomas ecosystem, a locality lacking floristic information in the Virú province, La Libertad region, northern Peru. A baseline of vascular flora was established based on botanical collections and a review of herbarium samples from the study area. A total of 156 species were identified, distributed across three landscape units, of which 52 are endemic to Peru. New records are also presented, and a new combination in Echeandia (Asparagaceae) is proposed. The diversity of the study area is discussed in comparison with other localities nationwide, and a possible biogeographic connection between the coastal desert and high Andean ecosystems is also considered. A land-use change in the sandbanks is reported, a latent threat that agro-industrial crops pose to endemic lomas species with restricted distribution. The purpose of this study is to draw attention to a fragile ecosystem that clearly requires short and long-term conservation measures.